Assessment of rheumatoid activity based on clinical features and blood and synovial fluid analysis. Issue 2 (April 1976) - Farr, M; Kendall, M J; Young, D W; Meynell, M J; Hawkins, C F
Abstract : Joint inflammation in rheumatoid arthritis has been assessed, and the most useful guides to disease activity were determined by analysis of synovial fluid and blood together with the history of joint disability. The patient's own evaluation of the amount of pain suffered was the most useful clinical assessment. Differential cell count and glucose estimations were the most helpful guides in the synovial fluid, while C-reactive protein in the serum most accurately reflected disease activity. The effects of systemic steroids on these indices were studied, and the differences between seronegative and seropositive patients noted.